Propagation of Azolla pinnata as phytofertilizer in different water resources - Nordiah Bidin.
Azolla pinnata is a floating aquatic fern growing in tropical freshwater ecosystem. It has symbiotic nitrogen fixing cyanobacteria (Anabaena azollae) within its leaf cavities. A study on propagation of Azolla pinnata in different water resources has been conducted from May until July 2011 at Aquaculture Research Station, Puchong. The purpose of this study is to determine the suitability of different water resources for growing Azolla pinnata, to study the life cycle in selected water condition and to determine the mineral content of Azolla pinnata. Four types of water resources (waste water, drain water, paddy field water and distilled water) were used to propagate the Azolla pinnata without nutrient and with nutrient supplement. Drain water showed the best water resource for propagate Azolla pinnata without nutrient supplied with its number of plants produced is 5-4 leaves per week, the biomass yield production is 0.24 g/week and daily growth rate is 17.14 %. Azolla pinnata propagation in distilled water showed the best growth performance compared other waters with number of plants produced is 24-25 leaves per week, biomass yield production is 0.51 g/week and daily growth rate is 4.20 %. The life cycle 0 f Azolla pinnata in drain water is about 15-17 days. Minerals content of Azolla pinnata such as nitrogen, phosphorus and potassium were 3.08 %, 0.08 %, 2.68 % respectively. With high nitrogen content, this make Azolla pinnata is a valuable of phyto-fertilizer.